1991
DOI: 10.1038/ki.1991.180
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic changes in renal function following unilateral nephrectomy

Abstract: Free-flow micropuncture was used to assess proximal and distal tubular function in rats immediately (2 to 5 hours), five days and 30 days after uninephrectomy (UN); results were compared with those in sham-operated littermates. Excretion rates of water, sodium and potassium were approximately doubled in the remaining kidney of UN rats. Two to five hours after UN there were small increases in glomerular filtration rate (GFR) and single nephron GFR which at this stage were not accompanied by an increase in absol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
66
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 23 publications
9
66
1
Order By: Relevance
“…3 Because effectively, only 1 kidney is transplanted to bilaterally nephrectomized recipients in these experiments, a group of treated and CON animals were unilaterally nephrectomized (no transplantation) to control for the impact of a solitary kidney or the effect of compensatory renal growth (CRG) on the long-term level of arterial pressure. 3,16 As in our previous study, 35 no differences in left kidney mass were found between the groups after uninephrectomy, confirming that previous ACE inhibitor treatment does not alter the CRG response. Using the radiotelemetric blood pressure assessment, we also confirmed that uninephrectomy, with the associated CRG, has no effect on the level of arterial pressure in CON or previously treated SHRs.…”
Section: Discussionsupporting
confidence: 75%
“…3 Because effectively, only 1 kidney is transplanted to bilaterally nephrectomized recipients in these experiments, a group of treated and CON animals were unilaterally nephrectomized (no transplantation) to control for the impact of a solitary kidney or the effect of compensatory renal growth (CRG) on the long-term level of arterial pressure. 3,16 As in our previous study, 35 no differences in left kidney mass were found between the groups after uninephrectomy, confirming that previous ACE inhibitor treatment does not alter the CRG response. Using the radiotelemetric blood pressure assessment, we also confirmed that uninephrectomy, with the associated CRG, has no effect on the level of arterial pressure in CON or previously treated SHRs.…”
Section: Discussionsupporting
confidence: 75%
“…37,38 It remains possible that the low nephron number might itself predispose to the development of hyperuricemia as a consequence of an increase in proximal tubular reabsorption, which might stimulate UA reabsorption. 39 Finally, elevation of UA in the child could occur from genetic or environmental mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors, such as sodium delivery to the CCD (45,46) and mineralocorticoid (47), could be responsible for the adaptive increase in Na+ and K+ transports in the CCDs from the contralateral kidney. In addition, growth factors ( 17) may also be involved in the mechanisms of the adaptation after loss of functional nephron.…”
Section: Control Uuook Uuocmentioning
confidence: 99%